Celestina - Rojas, Fernando de, -1541 (Margellos world republic of letters book., 2009)
A timeless story of love, morality, and tragedy, Fernando de Rojas's Celestina is a classic of Spanish literature. Second only to Don Quixote in its cultural importance, Rojas's dramatic dialogue presents the elaborate tale of a star-crossed courtship between the young nobleman Calisto and the beautiful maiden Melibea in fifteenth-century Spain. Their unforgettable saga plays out in vibrant exchanges, presented here in a brilliant new translation by award-winning translator Margaret Sayers Peden. After a chance encounter with Melibea leaves Calisto entranced by her charms, he enlists the services of Celestina, an aged prostitute, madam, and procuress, to arrange another meeting. She promptly seizes control of the affair, guiding it through a series of mishaps before it meets its tragic end. At times a comic character and at others a self-assertive promoter of women's sexual license, Celestina is an inimitable personality with a surprisingly modern consciousness, certain to be relished by a new generation of readers.